Prevalence of Congenital Malaria in Minna, North Central Nigeria. (14th August 2011) - Omalu, Innocent Chukwuemeka James; Mgbemena, Charles; Mgbemena, Amaka; Ayanwale, Victoria; Olayemi, Israel Kayode; Lateef, Adeniran; Chukwuemeka, Victoria I.
Abstract : The study was designed to determine the true prevalence of congenital, cord, and placental malaria in General Hospital Minna, North Central Nigeria. Peripheral blood smears of near-term pregnant women, as well as the placental, cord, and peripheral blood smears of their newborn babies, were examined for malaria parasites, using the Giemsa staining technique. Out of 152 pregnant women screened, 21 (13.82%) of them were infected with malaria parasites. Of the 152 new born babies, 4 (2.63%) showed positive peripheral parasitaemia. Placental parasitaemia was 7/152 (4.61%), while cord blood parasitaemia was 9/152 (5.92%). There were strong associations between peripheral and cord malaria parasitaemia and congenital malaria (P < 0.05 ). Plasmodium falciparum occurred in all, and none had mixed infection. The average birth weights of the babies delivered of nonmalarious pregnant women were higher than those delivered by malarious pregnant women, though not significant (P > 0.05 ). Malaria parasitaemia occurred more frequently in primigravidae than multigravidae.